1996
DOI: 10.1044/jshr.3904.839
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Abilities of Children With Specific Language Impairment

Abstract: A 2-year follow-up of the mathematical abilities of young children with specific language impairment (SLI) is reported. To detect the nature of the difficulties children with SLI exhibited in mathematics, the first- and second-grade children's performance was compared to mental age and language age comparison groups of typically developing children on a series of tasks that examined conceptual, procedural, and declarative knowledge of mathematics. Despite displaying knowledge of many conceptual aspects of math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
3
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 48 publications
4
68
3
4
Order By: Relevance
“…for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used Number Skills in Children with SLI 8 to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 96%
See 3 more Smart Citations
“…for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used Number Skills in Children with SLI 8 to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 96%
“…Children with SLI have a less developed store of arithmetic facts than that of age-matched children (Cowan et al, 2005;Fazio, 1996), a difference which persists during development. For instance, Fazio (1996Fazio ( , 1999 found that children with SLI evaluated at the age of 7 were still less efficient three years later. Furthermore, they made more errors and were slower than age-matched children at solving more complex calculation problems, and they tended to use a higher proportion of immature calculation strategies (e.g., finger counting) for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006).…”
Section: Number Skills In Children With Slimentioning
confidence: 99%
See 2 more Smart Citations
“…Fazio (1994Fazio ( , 1996Fazio ( , 1999 suggests that working memory deficits are mainly responsible for the deficits in counting and knowledge of number facts that children with SLI show.…”
Section: Working Memorymentioning
confidence: 99%